Penerapan Metode Storytelling Dalam Pembelajaran Keterampilan Berbicara Bahasa - Ahmad Sani; Al Qadri, Muhammad; Rizkyta, Atadya Putri; Nurul Izzah (ABANNA: Journal Of Contemporary Islamic Education, 2025)
Speaking skill (maharah kalām) is a key indicator of success in Arabic language learning as it requires the integration of vocabulary, grammar, pronunciation, and communication fluency. However, learning in madrasahs and Islamic boarding schools often focuses on receptive skills such as reading, resulting in relatively low oral communication abilities among students. Previous studies indicate that the main obstacles stem from monotonous teaching methods and the lack of interactive media. The storytelling method is considered a potential solution, as it encourages students to listen, comprehend, and retell stories creatively, thereby enhancing motivation, enriching vocabulary, and fostering speaking confidence. This study aims to analyze the effectiveness of storytelling in improving maharah kalām, identify supporting and inhibiting factors, and formulate an integrative learning model suitable for the educational context in Aceh. The research employed a qualitative descriptive approach through library research. Data were collected from journals, books, and relevant research reports published in the last ten years, and analyzed using content analysis techniques. The results reveal that storytelling effectively improves maharah kalām by strengthening vocabulary, pronunciation, and grammar within a complete discourse context. Supporting factors include relevant story content, teacher competence, availability of learning media, and a conducive learning environment. Inhibiting factors include limited time, varying student abilities, and insufficient teacher training. The novelty of this study lies in contextualizing storytelling for madrasahs/pesantren in Aceh and integrating it with a gradual reinforcement of linguistic elements. Further studies using experimental or action research designs are recommended to empirically validate the model’s effectiveness.